Chatter Dynamics on Impulse Surfaces in Impulsive Differential Systems - Zheng, Shasha; Fu, Xilin (Journal of Applied Nonlinear Dynamics, 2026)
In this article, we discuss the pulse phenomena for a class of impulsive differential systems from the angle of discontinuity, consider the systems as a global discontinuous one consisting of two uniquelycontinuous subsystems and investigate its chatter dynamics. We introduce the method of flow theory and focus on the dynamical behaviors on the impulse surface. By deliberating analytical criteria for the transversality of a flow to the boundary surface, some sufficient conditions that guarantee the absence of pulse phenomena are obtained. We generalize several known results and some examples are given to apply the theory.